АНГЛОМОВНА ВИЩА ОСВІТА В ЄВРОПЕЙСЬКОМУ СОЮЗІ - Мосьпан, Наталя (Збірник наукових праць Уманського державного педагогічного університету, 2020)
Стаття розглядає проблеми поширення англійської мови в глобальному контексті в університетському навчанні Європейського Союзу. У статті аналізуються рушійні сили англоїзації Європейської вищої освіти та вплив англомовної освіти в Європі. Основою для аналізу є дослідження професора Дж А. Коулмана, який намагався виміряти ступінь англоїзації Європейської вищої освіти та дослідити його можливі майбутні тенденції. У статті наведені причини та сучасний стан англомовної освіти у різних частинах Європи. Статья рассматривает проблемы распространения английского языка в глобальном контексте в университетском обучении Европейского Союза. В статье анализируются движущие силы англоизации Европейского высшего образования и влияние англоязычного образования в Европе. Основой для анализа является исследование профессора Дж. А. Коулмана, который пытался измерить степень англоизации Европейского высшего образования и исследовать его возможные будущие тенденции. В статье приведены причины и современное состояние англоязычного образования в разных частях Европы. The use of English is widespread due to economic, political and strategic alliances, scientific, technological and cultural ties, masss-media, international corporations, improved conditions of communication, internationalization of professional and personal activities. This article considers the spread of English in the global context in the university education of the European Union. This article analyzes the driving forces of English-medium teaching in European higher education and the influence of English education in Europe. The basis for the analysis is the study of Professor James A. Coleman, who tried to measure the degree of the extent to which English is progressively becoming ‘the language of higher education’ in Europe, to assess the extent of this phenomenon and to examine its possible future trends. This article describes the global context within spread of English as a lingua franca and marketization of higher education. Here are given the reasons and the current state of Englishmedium in higher education institutions in different parts of Europe.